Game-theoretical analysis for choosing the topology in multi-loop control systems - Wellenreuther, Andrea; Gambier, Adrián; Badreddin, Essameddin (2008 American Control Conference, 2008)
Abstract—The focus of the paper is the review of the control structure selection for a given system. If a framework, derived from game theory is used for the control system design of multiloop systems, the question arises, how unequally distributed or incomplete information affects the selection of the players strategies. In the field of game theory, information is an essential component. Different information sets lead to different strategy selections provided by the controllers and the belonging control laws. In the present paper, an asymmetric triangular multiloop control structure was chosen as basis to study and discuss the effects of different information sets to the solution of each game. The solution of the game provides a Pareto-optimal set of controller parameters for the multi-loop control system.